Penataan Ulang Area Produksi Industri Rumah Tangga Kabupaten Bekasi - Sari, Dessy Agustina; Hakiim, Azafilmi; Irawan, Riyant; Dewi, Rosita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Betawi’s taffy made of sticky rice was one of the best economic commodities for sub-district Cibitung’s citizens. Furthermore, this product usually gave success in a yearly exhibition for district Bekasi. For a long time, demand a trust the costumers were longer completed through the serving of nutrient food and the hygiene concept. That became a challenge for the owner and the Sukajaya village’s leader to decrease the resellers. Afterward, the breakthrough way guided selling the product into the food and the gift store in the scale of the home industry, which attached the label below monitoring the Service of Healthy (P-IRT). Achieve that, the initial step has been done that supported the guiding in the Sukajaya village and LPPM Unsika. The next activity for the site work evaluation also has been executed. It is such as providing a base for raw material until product and cover for the roof in around production line, giving the name for each section place, and pin the license certificate. Neat and clean aspects gave an esthetic point. Furthermore, it positively affected the occupation program of Sukaya village in the district Bekasi level.